5PSQ-019 An organisational approach to improve the safety of intravenous potassium chloride replacement: data from a tertiary care hospital. (2nd March 2018) - Fakhir, J; Ghanem, W Abi; Ramia, E; Khoury, C El; Issa, S; Skayem, N
Abstract : Background: Since 1999, institutions have been highly encouraged to provide special safeguards to reduce the risk of errors associated with potassium chloride (KCl) concentrate for injection such as removing concentrated KCl from floor stock and using commercially available premixed intravenous solutions. In some healthcare institutions, the implementation of these strategies are still lagging behind, and KCl concentrates for injection still pose safety threats to patients. Purpose: The aim of the project was to standardise the ordering and administration of intravenous KCl across a tertiary care hospital, and improve patient safety. Material and methods: The project consisted of a screening phase (September 2015 to January 2016), an interventional phase consisting of the introduction of KCl premixed bags to the hospital formulary in January 2017 and an evaluation phase post-implementation (February to April 2017). The target population consisted of adult patients prescribed intravenous KCl in the Internal Medicine, Intensive Care and Geriatrics units. The data collection form included patient information and intravenous KCl administration details. The evaluation phase also included focus-group discussions with different medical teams. Descriptive statistics were used to report the different findings. Results: In the screening phase, 249 KCl orders were examined. Twenty-three different dilutions of KCl orders were administered. Discrepancies identified included administering higher than the recommended dose for 17.3% of the patients, and administering rates of 15 mEq/hour of intravenous KCl without central catheter and cardiac monitor. In January 2017, KCl concentrates were removed from most clinical wards, and five commercially available premixed intravenous solutions of KCl were introduced to the hospital formulary. In the post-implementation phase, the variations in the dilutions decreased noticeably, but several discrepancies were identified such as the need for different premixed dilutions to serve specific populations such as patients with hypernatraemia and volume restriction, patients with diabetic ketoacidosis and the potential need to keep KCl concentrates for injection in some clinical wards such as dialysis units. Conclusion: The implementation of a standardised protocol for the ordering, preparation and administration of intravenous KCl is essential in reducing the associated patient safety threats. Healthcare institutions are entrusted to provide special safeguards to reduce the risk of errors. References and/or Acknowledgements: Institute of Safe Medication Practice. No conflict of interest